The Effect of Comorbid Conditions on Mortality in Patients Undergoing Percutaneous Coronary Intervention - Afzal, Zeeshan; Khan, Farhat Ullah; Khan, Muhammad Idrees; Akhtar, Syed Ahsan; Ayub, Asfandyar; Hafeez, Muhammad (Indus Journal of Bioscience Research, 2025)
Introduction: Percutaneous coronary intervention (PCI) forms a standard treatment approach for coronary artery disease (CAD), while comorbid conditions produce considerable effects on patient results. Research determines how comorbidities affect the survival rates of patients who receive PCI. Objective: The research aims to determine how comorbidities affect the death rates of patients who receive PCI both during hospitalization and in the long-term. Materials and Method: A retrospective cohort research took place at Department of Cardiology, Hayatabad Medical Complex, Peshawar from January, 2022 to June of 2022. The study examined a total of 150 PCI patients' medical information including their diagnoses of heart failure and chronic kidney disease and COPD. The research used mortality data in combination with the Charlson Comorbidity Index (CCI) for measuring patient outcomes. Results: The mortality rate in hospitals reached 5.3%, while patients who had both heart failure and chronic kidney disease experienced the highest risk factors. Long-term mortality data computed 3.6% death amongst all patients, though COPD and kidney disease combination increased fatality rates. Conclusion: Healthcare providers need a unique treatment approach to care for PCI patients before their procedure because their coexisting illnesses raise the possibility of hospital deaths and reduced long-term survival chances.